The kingdom among us : the gospel according to Dallas Willard - Robb, Michael Stewart (Minneapolis, MN : Fortress Press, 2022)
Despite perennial attraction to his teachings, Dallas Willard's theology has not been easy for his readers and colleagues to figure out or piece together. His approach to theology was an odd one. His five bestselling books on the Christian life were a "side job" to his quiet career as a professional philosopher. To what, if not to his profession, can one attribute the lasting attraction of his books? On one hand, it is Willard's rhetorical skill and his cross-disciplinary knowledge--philosophical, psychological, biblical--regarding the central issues of human life. But more importantly, his books all proclaim a gospel which in the late twentieth and early twenty-first centuries can be especially hard to hear. Willard spoke of this gospel in biblical terms, "the gospel of the kingdom," a gospel of spiritual living. The Kingdom Among Us presents a comprehensive account of that gospel. But it is much more than mere interpretation. By examining both Willard's writings and hundreds of hours of audio recordings, Michael Steward Robb both recovers and expands Willard's theological vision. The book will help long time readers of Willard's books make sense of his position in professional theology and philosophy. Robb's reconstruction of a gospel of spiritual living will help scholars, theologians, and philosophers make sense of Willard's "side job." But all readers will encounter in these pages the most complete picture available of one of the giants of modern Christian spirituality.
Introduction. The odd duck of twentieth-century theology -- Part I. In search of biblical ontology. The first listeners' eye view -- The ontological approach to the Bible -- Theology and the objectivity of faith -- Part II. The first stage. What the Jews knew -- Jesus's popularity, explained -- Part III. The second stage. What else the Jews knew (or could have) -- The (lost) gospel of Jesus the teacher -- The (only) gospel that makes disciples -- Part IV. The third stage. What a few Jews knew -- The king and soteriological déjà vu -- Cur deus homo? -- Conclusion. The odd duck for twenty-first century theology.
Includes bibliographic references and indexes.
Description based on online resource; title from digital title page (viewed on August 15, 2022).
JSTOR
Keywords: Willard, Dallas, -- 1935-2013.; Jesus Christ -- Teachings; Jésus-Christ -- Enseignements; Willard, Dallas, -- 1935-2013; Willard, Dallas, -- 1935-2013.; Jesus -- Teachings; Theology, Doctrinal -- History -- 20th century; Spirituality -- Christianity; Christian life; Vie chrétienne.; Théologie dogmatique -- Histoire -- 20e siècle.; Spiritualité -- Christianisme; Philosophy; RELIGION; Systematic; Christian Theology; Christian Life; Christian life; Theology, Doctrinal -- History -- 20th century; Spirituality -- Christianity; Electronic books; History